Characterization of Cellular and Molecular Heterogeneity of Bone Marrow Stromal Cells - Mona Elsafadi; Muthurangan Manikandan; Muhammad Atteya; Jamil Amjad Hashmi; Zafar Iqbal; Abdullah Aldahmash; Musaad Alfayez; Moustapha Kassem; Amer Mahmood (Hindawi Limited, 2016)
Human bone marrow-derived stromal stem cells (hBMSC) exhibit multiple functions, including differentiation into skeletal cells (progenitor function), hematopoiesis support, and immune regulation (nonprogenitor function). We have previously demonstrated the presence of morphological and functional heterogeneity of hBMSC cultures. In the present study, we characterized in detail two hTERT-BMSC clonal cell populations termed here CL1 and CL2 that represent an opposing phenotype with respect to morphology, markers expression: alkaline phosphatase (ALP) and CD146, and ex vivo differentiation potential. CL1 differentiated readily to osteoblasts, adipocytes, and chondrocytes as shown by expression of lineage specific genes and proteins. Whole genome transcriptome profiling of CL1 versus CL2 revealed enrichment in CL1 of bone-, mineralization-, and skeletal muscle-related genes, for example, ALP, POSTN, IGFBP5 BMP4, and CXCL12. On the other hand, CL2 transcriptome was enriched in immune modulatory genes, for example, CD14, CD99, NOTCH3, CXCL6, CFB, and CFI. Furthermore, gene expression microarray analysis of osteoblast differentiated CL1 versus CL2 showed significant upregulation in CL1 of bone development and osteoblast differentiation genes which included several homeobox genes: TBX15, HOXA2 and HOXA10, and IGF1, FGFR3, BMP6, MCAM, ITGA10, IGFBP5, and ALP. siRNA-based downregulation of the ALP gene in CL1 impaired osteoblastic and adipocytic differentiation. Our studies demonstrate the existence of molecular and functional heterogeneity in cultured hBMSC. ALP can be employed to identify osteoblastic and adipocytic progenitor cells in the heterogeneous hBMSC cultures.